2016
DOI: 10.18632/oncotarget.7018
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TFAM inhibits the tumorigenesis of non-small cell lung cancer by activating ROS-mediated JNK/p38MAPK signaling and reducing cellular bioenergetics

Abstract: Mitochondrial transcription factor A (TFAM) is essential for the replication, transcription and maintenance of mitochondrial DNA (mtDNA). The role of TFAM in non-small cell lung cancer (NSCLC) remains largely unknown. Herein, we report that downregulation of TFAM in NSCLC cells resulted in cell cycle arrest at G1 phase and significantly blocked NSCLC cell growth and migration through the activation of reactive oxygen species (ROS)-induced c-Jun amino-terminal kinase(JNK)/p38 MAPK signaling and decreased cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 37 publications
(36 reference statements)
13
56
0
Order By: Relevance
“…It was reported that TFAM depletion could result in upregulation of the levels of proapoptotic Bax, p21, tumor suppressor p53, and p-p53 (ser15), as well as poly ADP ribose polymerase (PARP), caspase 3 and caspase 9 cleavage [16]. In our study, TFAM knockdown by miR-214 mimic could reduce NF-κB nuclear translocation in vivo and in vitro.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 52%
See 3 more Smart Citations
“…It was reported that TFAM depletion could result in upregulation of the levels of proapoptotic Bax, p21, tumor suppressor p53, and p-p53 (ser15), as well as poly ADP ribose polymerase (PARP), caspase 3 and caspase 9 cleavage [16]. In our study, TFAM knockdown by miR-214 mimic could reduce NF-κB nuclear translocation in vivo and in vitro.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 52%
“…Previous report demonstrated that down-regulation of TFAM in non-small cell lung cancer could activate reactive oxygen species (ROS)-mediated c-Jun N-terminal kinase(JNK)/ p38 mitogen-activated protein kinase (MAPK) signaling and reduce cellular bioenergetics which resulted in cell cycle arrest [16]. It was found in this study that TFAM expression could lead to the enhanced NF-κB activity as well as the promoted NF-κB dependent gene expression.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 63%
See 2 more Smart Citations
“…A previous study also revealed that antioxidants may effectively restrain ROS generation and apoptosis caused by UVA (28). The generated ROS activates the upstream activating agent and apoptosis signal conditioning kinase 1 (AsKI) of p38 and c-Jun N-terminal kinase, so as to activate p38, indicating that ROS-ASKI-p38MAPK pathway is an important signal transduction pathway in the carcinogenic effects of ultraviolet light (29). In the present study it was revealed that salvianolic acid B increased ROS generation levels and the silencing of p38 expression inhibited the anticancer effect of salvianolic acid B on the level of ROS generation in the MG63 cell line.…”
Section: Discussionmentioning
confidence: 96%